We are decolonizing the pulpit: Discursive postures of Pentecostal-styled preachers venerating ancestors in South Africa - Khanyile, Sphesihle Blessing (Center for Sociological Studies and Community Developmen, 2025)
South Africa has recently experienced a new religious vitality. Apparently, select Pentecostal-style preachers are embracing syncretic technologies and discourses. These blatantly counter-biblical narratives are heavily charged with aspirations to decolonize the pulpit and reclaim African spiritualities and reform mentalities. Forbidden practices of ancestor worship have emerged as important accommodations to express African methodologies of spirituality, cosmology, and thought. The play examines a preacher from South Africa who brazenly promotes this shunned accommodation. Prophet Magejageja re-articulates biblical textuality to traverse a decolonial horizon. The preacher knowingly commits doctrinal suicide by contradicting his Pentecostal theological heritage in order to promote something religiously innovative. The preacher encourages a return to the past, even though Pentecostalism enthusiastically calls for a break with the past because of evil and retrogressive associations with the past. Four YouTube sermons are linguistically examined using thematic critical discourse analysis with the aim of elucidating the preacher's decolonially charged pulpit language tropes. Key findings reveal entanglements of multiple ideological discourses: Post-Christianity, Afrocentrism, Counter-Pentecostalism, Missionary Critique, Black Consciousness, Pan-Africanism, Black physical liberation, anti-inferiority complexes, and counter-narratives to Western oppression in Africa. His syncretistic register undoubtedly underscores that the new media facilitate the possibility of undermining the insidious life of the coloniality of power.